Quality of life and perceived health status in surviving adults with univentricular heart. Issue 1 (1st July 2001) - Saliba, Z; Butera, G; Bonnet, D; Bonhoeffer, P; Villain, E; Kachaner, J; Sidi, D; Iserin, L
Abstract : OBJECTIVE: To evaluate the quality of life in patients with univentricular heart and to determine the impact of sociodemographic and clinical characteristics. DESIGN AND SETTING: Retrospective, cross sectional study conducted in a regional paediatric cardiology centre. PATIENTS: The health records of 89 survivors with univentricular heart (median age 21 years; range 17–49 years) were reviewed. Sixty seven answered the Duke questionnaire. Sociodemographic and clinical variables were similar in the responders and non-responders. The impact of sociodemographic and clinical variables on individual Duke's measures was assessed. RESULTS: The Duke scores of adults with univentricular heart were similar to the normal population. Cyanosis predicted a worse score for physical (p = 0.05) and perceived health measures (p = 0.02). A higher educational level predicted a better score for physical (p = 0.004), mental (p = 0.01), and general health measures (p = 0.02). Orthopaedic problems worsened the social score (p = 0.05). Psychosocial problems worsened the pain score (p = 0.04). In comparison with the other anatomical types, mitral atresia worsened the perceived health score (p = 0.02). Patients younger than 23 years scored better for almost all health and dysfunction measures. CONCLUSIONS: Despite repeated interventions and other disease related everyday stresses, a selected group of adults with univentricular heart had a satisfying quality of life.